2013
DOI: 10.1021/ol403041k
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Conjugate Addition of Acyl Anion Equivalents Promoted by Fluorodesilylation

Abstract: The conjugate addition of acyl anion equivalents derived from 2-silyl-1,3-dithianes to α,β-unsaturated ketones and esters has been achieved using a substoichiometric amount of TBAF. High yields and short reaction times are observed for the addition of aryl-1,3-dithianes to a variety of cyclic and acyclic α,β-unsaturated carbonyl acceptors. Observation of the reactive anion by (13)C NMR spectroscopy and extension to an asymmetric variant is also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…There has been considerable interest in development of new types of umpolung reagents due to their utility in accessing carbonyl compounds having 1,4 functional group relationships. 21,22 Given the facile reactivity of 1 as soft nucleophiles (Scheme 1-2) and the mild conditions required for oxidation of boronate group, 12,15 we hypothesized that a one-pot conjugate addition-diboron oxidation sequence could be feasible. The resulting 1,4-dicarbonyl products are privileged intermediates for synthesis of bioactive compounds.…”
Section: One-pot Diboron Conjugate Addition-oxidation γ-Keto Acylboronmentioning
confidence: 99%
“…There has been considerable interest in development of new types of umpolung reagents due to their utility in accessing carbonyl compounds having 1,4 functional group relationships. 21,22 Given the facile reactivity of 1 as soft nucleophiles (Scheme 1-2) and the mild conditions required for oxidation of boronate group, 12,15 we hypothesized that a one-pot conjugate addition-diboron oxidation sequence could be feasible. The resulting 1,4-dicarbonyl products are privileged intermediates for synthesis of bioactive compounds.…”
Section: One-pot Diboron Conjugate Addition-oxidation γ-Keto Acylboronmentioning
confidence: 99%
“…In contrast to 1,4‐dicarbonyls in general, the synthesis of 1,4‐diketones poses a greater challenge, often requiring use of an excess of one coupling partner and/or significant pre‐functionalisation of substrates to achieve the desired heterocoupling. Reported methods include oxidative homocoupling [23–27] or heterocoupling of ketone enolates, [7,24,28–34,35,36] alkylation of enolates, [9,14,37–42] alkylation of acyl anion equivalents [43–47] or acyl radicals, [11,48] acylation of homoenolate equivalents, [12,13,49–52] or multicomponent strategies [53,54] . Only a subset of methods have been reported that tolerate aliphatic substrates for both reaction partners: addition of silyl enolates to oxyallyl zwitterions [10] and the aldehyde umpolung‐based Stetter reaction [4,5,45,55] …”
Section: Figurementioning
confidence: 99%
“…[8,[15][16][17][18][19][20][21][22] In contrast to 1,4-dicarbonyls in general, the synthesis of 1,4-diketones poses a greater challenge, often requiring use of an excess of one coupling partner and/or significant pre-functionalisation of substrates to achieve the desired heterocoupling. Reported methods include oxidative homocoupling [23][24][25][26][27] or heterocoupling of ketone enolates, [7,24,[28][29][30][31][32][33][34]35,36] alkylation of enolates, [9,14,[37][38][39][40][41][42] alkylation of acyl anion equivalents [43][44][45][46][47] or acyl radicals, [11,48] acylation of homoenolate equivalents, [12,13,[49][50][51][52] or multicomponent strategies. [53,…”
mentioning
confidence: 99%
“…In general, α,β-unsaturated carbonyl compounds constitute one of the most frequently used electrophiles that readily accommodate an appropriate nucleophile . Nevertheless, alternative synthetic methods have been developed for the successful formation of allenol/allenolates or vinyl carbanions from α,β-unsaturated compounds .…”
mentioning
confidence: 99%